Kode Vicious. - Neville-Neil, George V. (Communications of the ACM, 2012)
The author argues that the IP Firewall (IPFW) code written by the computer scientist Luigi Rizzo effectively reuses subsystems and functions to manage data packets and also argues against the use of profanity in code in response to a question from a reader. Topics include integrated development environment (IDE) software, computer programming, and optimizing compilers.